Approaches to Exchange Rate Policy. (International Monetary Fund, 1994)
External sector policies and exchange rate policy are central to a country's economic performance and to the IMF's surveillance functions. The papers in this book, edited by Richard Barth and Chorng-Huey Wong, were presented at a seminar on Exchange Rate Policy in Developing and Transition Economies held by the IMF Institute. They analyze choices of exchange rate regimes, issues affecting management of exchange regimes, and specific types of regimes, including case studies from the former Soviet Union, Africa, Asia, and Latin America.